First Report of Three kinds of Mycotoxins Dioxynivalenol, Nivalenol and Fumonisin B2 in Seeds of Seven Wheat Cultivars in Iraq.: Mohammed Hussein Minati and Mohanned Khalaf Mohammed-Ameen - Minati, Mohammed Hussein (The Iraqi Journal of Veterinary Medicine, 2019)
This study was conducted to detect and quantify three mycotoxins Dioxynivalenol, Nivalenol and Fumonisin B2 in seeds of seven wheat cultivars planted in 17 wheat fields in Basra province, Iraq. This was done by using High Performance Liquid chromatographs analysis. The results revealed that Fumonisin B2 was the predominant mycotoxin, which present in 10 fields. The lowest concentration rate of this mycotoxin was 110 µg/Kg and the maximum was 11,228 µg/Kg. Dioxynivalenol as a trichothecene was in the second level detected in 6 fields with a minimum concentration of 8 µg/Kg and a maximum of 1,060 µg/Kg. Nivalenol was found only in 4 fields ranging from 272-1900 µg/Kg. Fumonisin B2 Only three fields showed co-occurrence of two mycotoxins (Fumonisin B2 and Nivalenol) in each, but with various concentration rates. The seven cultivars tested in this study were varied in their reactions to subjected mycotoxins. Adana 99 (A. 99) cultivar showed the highest concentration rate of both Fumonisin B2 and Nivalenol, which present with average percentage of 64% and 58% respectively. While, for Dioxynivalenol, Ebaa 99 (E.99) was on the top, it occurred in 6 fields ranging from 8-1060 µg/Kg with an average percentage of 43%.